2023
DOI: 10.3847/2515-5172/acefc4
|View full text |Cite
|
Sign up to set email alerts
|

No UV-bright Eruptions from SN 2023ixf in GALEX Imaging 15–20 yr Before Explosion

Nicholas Flinner,
Michael A. Tucker,
John F. Beacom
et al.

Abstract: We analyze pre-explosion ultraviolet imaging of the nearby Type II supernova SN 2023ixf in search of precursor variability. No outbursts are seen in observations obtained 15–20 yr prior to explosion to a limit of L NUV ≈ 1000 L ⊙ and L FUV ≈ 2000 L ⊙. The time period of these non-detections roughly corresponds to changes in the circumstellar density inferred from early spectra and photometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Neustadt et al (2023) found that transient with peak luminosity >2 × 10 39 erg −1 cannot happen during 1-15 yr before the SN explosion. Higher nondetection limits can be also seen in Flinner et al (2023) in ultraviolet bands.…”
Section: Mass-loss Ratementioning
confidence: 93%
“…Neustadt et al (2023) found that transient with peak luminosity >2 × 10 39 erg −1 cannot happen during 1-15 yr before the SN explosion. Higher nondetection limits can be also seen in Flinner et al (2023) in ultraviolet bands.…”
Section: Mass-loss Ratementioning
confidence: 93%
“…These findings indicate that the progenitor of SN 2023ixf is fairly luminous compared to previously observed RSG SN progenitors, suggesting a massive RSG (e.g., Smartt 2015). Using archival Galaxy Evolution Explorer data, Flinner et al (2023) explore the near-and far-ultraviolet activity of the progenitor of SN 2023ixf up to 20 yr prior to the explosion, finding no outbursts in the UV to limits of L NUV = 1000 L e and L FUV = 2000 L e . Dong et al (2023) investigate the pre-SN photometry obtained with the Zwicky Transient Facility (ZTF), the Asteroid Terrestrial-impact Last Alert System (ATLAS), and DLT40.…”
Section: Introductionmentioning
confidence: 63%
“…Other investigations into pre-SN outbursts in SN 2023ixf also have not found evidence for any detectable signatures (Flinner et al 2023;Neustadt et al 2024;Panjkov et al 2023), although to varying limits. Our outburst constraints and photometric limits are comparable to those found by Dong et al (2023), who derive an upper limit to the ejecta mass of 0.015 M e based on the models of Tsuna et al (2023; compared to our ejecta mass limit of <0.3 M e ) for a hydrodynamical model that had peak M r ; −8 mag.…”
Section: Searching For Presupernova Outbursts With a Neural Net Class...mentioning
confidence: 88%
“…Ransome et al (2023) also found no significant detections in long-baseline, multiband Pan-STARRS light curves prior to explosion. Flinner et al (2023) also ruled out luminous UV eruptions 15-20 yr prior to explosion. Dong et al (2023) examined over ∼5 yr of preexplosion data from the DLT40, Zwicky Transient Facility, and ATLAS surveys and also concluded that the probability of precursor outbursts is low.…”
Section: Further Thoughtsmentioning
confidence: 99%